Richard Castle's Deadly Storm : a Derrick Storm mystery - Castle, Richard (Marvel Enterprises, 2011)
This 'adaptation' of Derrick Storm's first novel takes the hero from the gritty world of the private eye all the way to the globe-hopping intrigue of the CIA.